HUBUNGAN POLA KONSUMSI LEMAK DAN KEBIASAAN MINUM KOPI DENGAN HIPERTENSI PADA LANSIA DI KELURAHAN PEGUYANGAN KECAMATAN DENPASAR UTARA - Wulan Tri Utami; I Made Rodja Suantara; A.A.Gde Raka Kayanaya (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Relationship of Fat Consumption PatternsAnd Coffee Drinking HabitsWith Hypertension In the ElderlyIn Kelurahan Peguyangan, North Denpasar DistrictABSTRACTHypertension can be caused by various factors such as the age, sex, stress, patterns of excessive fat consumption and heredity. This research was conducted in May 2018, proportional random sampling technique was used to find 50 samples. there were 50.0% had hypertension and 50.0% were categorized as non-hypertensive. Based on research that has been done, there are 66.0% with age range 60-69 years and 34% with age 70 years, where 42,0% of them are male and the rest 58,0% are women. Based on the pattern of fat consumption, all samples consumed in both saturated and unsaturated fats based on the amount of fat consumed noted that 40.0% is sufficient and 60.0% less and based on frequent consumption of dietary fat sources 28.0% frequently and 72% rarely. Based on the habit of drinking coffee 80.0% very often and 20.0% rarely consume coffee. there is a relationship between fat consumption patterns and hypertension but there is no relationship between coffee drinking habits with hypertension. so, to prevent hypertension we should limit the consumption of fat, especially saturated fats.Key words : Fat Consumption Patterns, Coffee Drinking Habits, Hypertension, Elderly